Trisomy 18: A survey of opinions, attitudes, and practices of neonatologists. Issue 10 (17th June 2016) - Jacobs, Adam P.; Subramaniam, Akila; Tang, Ying; Philips, Joseph B.; Biggio, Joseph R.; Edwards, Rodney K.; Robin, Nathaniel H.
Abstract : We conducted a survey‐based study of the opinions, attitudes, and management practices of neonatologists across the United States regarding prenatally diagnosed Trisomy 18. The survey was designed based on previously validated surveys of severe fetal anomalies and collected demographic information on participants, as well as their attitudes, and management choices given a series of vignettes beginning in the prenatal period. The survey was sent to 3, 143 American Academy of Pediatrics Section on Neonatal‐Perinatal Medicine members of which 409 (13%) completed the survey. While the response rate was rather low, our respondent pool was representative of the national neonatologist population. Respondents were predominately white (81%), married (88%), Christian (54%), had children (86%), and were pro‐choice in terms of abortion (68%). Eighty‐three percent (83%) of respondents thought that trisomy 18 is a lethal condition and 60% thought that treatment is futile. Seventy‐five percent (75%) expected that the best neurodevelopmental outcome in the case of infant survival would be profound intellectual disability. Regarding neonatal care, 95% stated that they would recommend palliative care only. Ninety‐five percent (95%) would never recommend or recommend only if asked full code resuscitation for a neonate with full trisomy 18, yet, 44% would comply partially or in full with a full code request for resuscitation measures. The demographic features that correlated most significantly with these responses were clinician race and years in practice. The attitudes toward and management of infants affected with trisomy 18 seem to be largely driven by parental attitudes and wishes. © 2016 Wiley Periodicals, Inc.